Evaluation of the vegetative and generative performance of new apple cultivars in the Nyírség region - Csihon, Á. (International Journal of Horticultural Science, 2014)
In this paper we examine apple varieties, which are planted expansively in the development apple orchards of the Western- European countries, but about its production characteristics we don’t have or just few practical experiences in Hungary. These varieties can be described with regular and high yields, aesthetic and alluring appearance in their origin places, what ensure profitable producing for the growers. Under the Hungarian climate which tends to be often extreme (hard cold winters, late spring frosts, summer drought, heat stress) these varieties may behave differently, so before the substantial planting it is expedient to carry out variety evaluations to avoid the later failures. The place of our experiments is located in the Nyírség representing adequately the ecological conditions of the surrounding areas, so the gained results can be adapted easily in the biggest apple production site of Hungary. Regarding the vegetative and the generative parameters of the 14 examined varieties (’Gala Venus Fengal’, ’Gala Decarli-Fendeca’, ’Galaval’, ’Jugala’, ’Gala Schnitzer (S) Schniga’, ’Red Cap Valtod (S)’, ’Early Red One’, ’Jeromine’, ’Crimson Crisp (Co-op 39)’, ’Red Topaz’, ’Wilton’s Red Jonaprince’, ’Red Idared’, ’Fuji September Wonder’, club cultivar) we found significant differences. The ratio of the thickness of trunk and the main branches showed that the trees have an optimal canopy structure in accordance with the Zahn principles, so they are in harmonious growing balance. The ‘Gala’ sport trained to slender spindle produced the highest yields, while the ‘Fuji’ and the ‘Red Delicious’ sport trained to super spindle can be described with the lowest values. All the cultivars reached the eating quality (65-70 mm), from which the ’Red Idared’, the ’Red Jonaprince’ and the ’Red Cap’ produced outstanding fruit size (81-85 mm).